2008
DOI: 10.1021/ja804185s
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning as a New Technique To Control the Crystal Morphology and Molecular Orientation of Polyoxymethylene Nanofibers

Abstract: Electrospinning is widely accepted as a simple and versatile technique for producing nanofibers. The present work, however, introduces a new concept of the electrospinning method for controlling the crystal morphology and molecular orientation of the nanofibers through an illustration of a case study of polyoxymethylene (POM) nanofibers. Isotropic and anisotropic electrospun POM nanofibers are successfully prepared by using a stationary collector and a rotating disk collector. By controlling the voltage and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
195
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(208 citation statements)
references
References 29 publications
13
195
0
Order By: Relevance
“…It has been reported that a gap in a charged collector induced polymer chain orientation within electrospun nanofiber [27]. Additionally, tensile force induced by rotating mandrel can also increase molecular alignment and crystallinity [28]. The improved elastic modulus achieved in this mandrel with gap may be strongly attributed to the enhanced molecular orientation and crystallinity, as demonstrated in the study of rotary jet electrospinning [23,24].…”
Section: Tensile Propertiesmentioning
confidence: 84%
“…It has been reported that a gap in a charged collector induced polymer chain orientation within electrospun nanofiber [27]. Additionally, tensile force induced by rotating mandrel can also increase molecular alignment and crystallinity [28]. The improved elastic modulus achieved in this mandrel with gap may be strongly attributed to the enhanced molecular orientation and crystallinity, as demonstrated in the study of rotary jet electrospinning [23,24].…”
Section: Tensile Propertiesmentioning
confidence: 84%
“…Electrospinning is capable of producing fibers with high strength [1] and large surface area-to-volume ratios [2]. An advantage of the process over conventional fiber forming methods is that only a small amount of polymer, as low as 50 mg, is required for electrospinning, in comparison to tens of kilogrammes of polymer required in conventional spinning methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of uniaxial orientation of PVA chains by electrospinning can be quantified by the dichroic ratio. 16 The dichroic ratio (R) is defined by the formula R ) A | /A ⊥ , where A | is infrared absorbance of the parallel component and A ⊥ is that of the perpendicular component. For a randomly oriented sample, R is equal to 1, and for a perfectly uniaxially oriented sample, R is equal to infinity.…”
Section: Resultsmentioning
confidence: 99%
“…11 The fibers are usually obtained as nonwoven mats; however, they can also be readily prepared as aligned arrays at the macroscopic level by using a collector consisting of two grounded conductive metal films separated by a millimeter-length air gap. 12,13 The electrical field applied during the spinning process enforces to orient the polymer chains at the molecular level [14][15][16] and as well as 1-dimensional constituent units in spinning solution such as wires, 17 tubes, 18 etc. Consequently, electrospinning is not only a robust technique to produce polymeric nanofibers but also a method to fabricate well-ordered nanostructured materials for various applications.…”
Section: Introductionmentioning
confidence: 99%